Cascade reaction–driven biomimetic scintillant/metal–organic frameworks for X-ray triggered combinational therapy against glioma - Lansheng Wang; Duo Xu; Xudong Hu; Rui Quan; Dong Lu; Zhen Li; Changshui Yu; Xingjun Li; Shuo Ma; Xiaoming Li; Zhengkui Zhang; Rutong Yu (Materials Today Bio)
Glioblastoma (GBM) is the most aggressive primary brain tumor with a grim prognosis and low survival rates. This unfavorable therapeutic outcome is partially because of the inadequate immune infiltration and an immunosuppressive microenvironment, which compromises the effectiveness of conventional radiotherapy (RT) and chemotherapy. Inducing immunogenic cell death (ICD) to modulate the antitumor immune response has emerged as a highly promising therapeutic strategy for GBM. Herein, we report the development of a novel radiodynamic therapy agent via an in situ growth strategy. This innovative agent integrates a porphyrin–hafnium metal–organic framework (MOF) with lanthanide scintillator nanoparticles (SNPs). Upon exposure to RT, the SNPs emit light, consequently activating the porphyrin photosensitizer. This mechanism circumvents the major limitation of poor light penetration through the scalp and skull, thereby enabling the effective delivery of photodynamic therapy to deep-seated tumor tissues. Concurrently, the hafnium enhances X-ray absorption, improving RT. This approach promotes tumor damage, triggers an immune response with ICD, dendritic cell maturation, and macrophage polarization. Additionally, the surface coating of nanoparticles with membranes derived from M1-polarized microglia allows them to efficiently cross the blood–brain barrier, enabling the precise targeting of GBM. Moreover, the costimulatory molecules present on these microglial membranes contribute to the remodeling of the immunosuppressive tumor microenvironment. Thus, RT-induced ICD combined with interleukin-12 therapy suppresses glioma recurrence. This nanoparticle system has potential as a dual-functional agent for GBM treatment.